Statistical analysis of fuel combustion and emissions considering the adverse effects of investment economic environment: Exploring alternatives amid oil prices Swings, digital economy, and local market inflation - Guo Yunli; Chen Chang; Na Ju (Heliyon, 2024)
The depletion of natural gas reserves, combined with rising oil prices, local market inflation, and concerns about pollution, has accelerated the search for alternative energy sources. As a result, research on turbines and internal combustion engines for electricity generation is increasingly focusing on using vaporized ethanol as a fuel substitute. However, the high cost of analyzing the chemical composition of these fuels often leads to an oversight of their impact on combustion characteristics, such as flame behavior, emission profiles, and temperature distribution.This study employs a statistical approach to assess the combustion and emission characteristics of biofuels, aiming to find suitable alternatives to petroleum-based fuels. By integrating considerations of oil price fluctuations and the digital economy's impact, the research proposes a cost-effective method for evaluating the chemical makeup of vaporized fuels and their effects on post-combustion pollution.Experimental data reveal that alternative fuels can offer stable ignition performance and lower pollution levels, contingent on their specific properties. Fuels with high aromatic content and viscosity tend to produce significant CO emissions, while reducing these characteristics may increase CO2 production. The study also highlights the challenge of simultaneously reducing both CO and NOx emissions. Additionally, the findings show that petroleum gasoline, due to its lower volatility, has favorable fire safety properties and generates fewer pollutants.In the context of economic pressures from rising oil prices and inflation, this research underscores the importance of exploring biofuels as viable, sustainable alternatives for the future energy landscape.